Emergency department management of traumatic brain injuries: A resource tiered review - Julia Dixon; Grant Comstock; Jennifer Whitfield; David Richards; Taylor W. Burkholder; Noel Leifer; Nee-Kofi Mould-Millman; Emilie J. Calvello Hynes (African Journal of Emergency Medicine, 2020)
Introduction: Traumatic brain injury is a leading cause of death and disability globally with an estimated African incidence of approximately 8 million cases annually. A person suffering from a TBI is often aged 20–30, contributing to sustained disability and large negative economic impacts of TBI. Effective emergency care has the potential to decrease morbidity from this multisystem trauma. Objectives: Identify and summarize key recommendations for emergency care of patients with traumatic brain injuries using a resource tiered framework. Methods: A literature review was conducted on clinical care of brain-injured patients in resource-limited settings, with a focus on the first 48 h of injury. Using the AfJEM resource tiered review and PRISMA guidelines, articles were identified and used to describe best practice care and management of the brain-injured patient in resource-limited settings. Key recommendations: Optimal management of the brain-injured patient begins with early and appropriate triage. A complete history and physical can identify high-risk patients who present with mild or moderate TBI. Clinical decision rules can aid in the identification of low-risk patients who require no neuroimaging or only a brief period of observation. The management of the severely brain-injured patient requires a systematic approach focused on the avoidance of secondary injury, including hypotension, hypoxia, and hypoglycaemia. Most interventions to prevent secondary injury can be implemented at all facility levels. Urgent neuroimaging is recommended for patients with severe TBI followed by consultation with a neurosurgeon and transfer to an intensive care unit. The high incidence and poor outcomes of traumatic brain injury in Africa make this subject an important focus for future research and intervention to further guide optimal clinical care.